Assessment of combination techniques in enhancing the regenerative potential of tricalcium phosphate graft in treatment of infrabony periodontal defects - Saini, Ashish; Singh, Meghna; Lal, Nand; Dixit, Jaya (Indian journal of dental research, 2011)
The purpose of the present study was to evaluate and compare the clinical outcome of infrabony defects following reconstructive surgery with the use of tricalcium phosphate (TCP) alone; TCP and citric acid (CA) root conditioning; and TCP, CA, and oxidized regenerated cellulose (ORC) membrane. Thirty-nine systemically healthy subjects with vertical infrabony defect were initially selected based on intraoral periapical radiographs and clinical examination to record probing pocket depth (PPD) and clinical attachment level (CAL). Only 21 defects revealed two-walled configuration on surgical debridement. These defects were selected and randomly allotted to the study groups. Group 1 defects were treated with TCP, group 2 with TCP+CA, and group 3 with TCP+CA+ORC. PPD, CAL, defect depth (DD), and level of alveolar crest (AC) were evaluated at the time of initial surgery and after 6 months at surgical re-entry. These measurements were utilized to calculate PPD reduction, CAL gain, defect fill (DF), %defect fill (%DF), and crestal resorption (CR). A paired t-test was used for assessing changes in each group. Unpaired t-test was used for intergroup comparisons. All three groups showed statistically significant PPD reduction, CAL gain, DF, and %DF, but insignificant CR at the end of 6 months. On intergroup comparison, no statistically significant differences were noted between the groups for all the parameters. Efficacy of combination techniques using TCP+CA; TCP+CA+ORC in treatment of periodontal infrabony defects is at least equal to that of TCP alone.